Model Test Study on the Antibreaking Technology of Reducing Dislocation Layer for Subway Interval Tunnel of the Stick-Slip Fracture - Guang-yao Cui; Xue-lai Wang (Advances in Civil Engineering)
Based on the background of the Line F2-3 interval tunnel section of Jiujiawan in Urumqi Subway Line 1, this paper carries out the model test research on the antibreaking technology of the reducing dislocation layer in the tunnel section of the stick-slip fracture. The antibreaking effect of different locations and number of reducing dislocation layers in tunnel engineering is analyzed in this paper. The results show that when the double reducing dislocation layer, respectively, set between the surrounding rock and the primary support, and the primary support and the secondary lining, the antibreaking effect is the best. It is recommended to use this scheme for antibreaking design. The research results can provide reference for antibreaking design of traffic tunnels in active fault zones.